Clients’ expectations from and satisfaction with medicine retail outlets in Gondar town, northwestern Ethiopia: a cross-sectional study - Workye M; Admasu S; Abura T; Belete Y; Getaye Y; Teni FS; Surur AS (Integrated Pharmacy Research and Practice, 2015)
Mulualem Workye,1 Sewunet Admasu,2 Tamrat Abura,1 Yared Belete,1 Yonas Getaye,2 Fitsum Sebsibe Teni,1 Abdrrahman Shemsu Surur31Pharmaceutics and Social Pharmacy Unit, 2Clinical Pharmacy Unit, 3Pharmaceutical Chemistry Unit, School of Pharmacy, College of Medicine and Health Sciences, University of Gondar, Gondar, Amhara Regional State, EthiopiaPurpose: The aim of this study was to assess clients' level of expectation from and satisfaction with medicine retail outlets (MROs) in Gondar town, northwestern Ethiopia.Patients and methods: An institutions-based cross-sectional study was conducted from April 20 to May 5, 2014, by sampling five pharmacies and eight drug stores through simple random sampling. Clients, 424, who came to the MROs during the study period were included in the study. Data were collected using structured questionnaires measuring expectations and satisfaction of clients using a Likert scale of 1–5 through face-to-face interviews.Results: Out of the total 424 interview encounters, 422 (99.5% response rate) questionnaires were included in the analysis, of which 61.1% were of males. The overall mean expectation of respondents toward MRO setting and services was 3.82 and that of satisfaction of the respondents was 3.02. More than three-quarters (76.8%) of the respondents expected medicines in affordable prices from MROs, but nearly half (44.8%) were not satisfied with it. Much more than half (58.5%) of the respondents were dissatisfied with the comfort and convenience of private counseling area. Also, nearly half (47.6%) of the respondents claimed that pharmacy professionals did not provide information regarding the storage condition of medications. There was statistically significant difference in overall expectation (t=2.707, P=0.007) and satisfaction (t=2.260, P=0.024) with the setting and services of MROs between respondents who claimed to know the difference between a pharmacy and a drug store and those who claimed they did not.Conclusion: Clients’ expectation from MRO services was high, with average satisfaction. The overall expectation and satisfaction of the respondents toward MROs were lower in those who reported they did not know the difference between a pharmacy and a drug store than in those who claimed to know the difference. Supportive supervision by the town’s health bureau on the MROs is recommended to help improve clients' satisfaction.Keywords: community, drug store, pharmacy, pharmacy professional, services